2013
DOI: 10.1179/0371955313z.00000000066
|View full text |Cite
|
Sign up to set email alerts
|

Compound formation in lanthanide–alkali metal halide systems

Abstract: The phase diagrams of trivalent lanthanide-alkali metal halide systems range from simple eutectic systems to systems with one or several congruently or incongruently melting compounds. Using both literature information and the authors' extensive experimental results, the LnX 3 -MX binary mixture phase diagrams were screened in terms of the IP Mz /IP Ln3z ratio (IP i : z i /r i ; z i : ionic charge; r i : ionic radius; Ln: lanthanide, X: halide and M: alkali metal). A similar approach was conducted on the dival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In addition, the diffusion coefficients of Eu 3+ and Eu 2+ are not the same. It has been reported that K 3 EuCl 6 is formed when EuCl 3 is added into KCl and K 2 EuCl 4 is formed with the addition of EuCl 2 to KCl, 29 which might cause the difference between the measured D Eu3+ and D Eu2+ .…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the diffusion coefficients of Eu 3+ and Eu 2+ are not the same. It has been reported that K 3 EuCl 6 is formed when EuCl 3 is added into KCl and K 2 EuCl 4 is formed with the addition of EuCl 2 to KCl, 29 which might cause the difference between the measured D Eu3+ and D Eu2+ .…”
Section: Resultsmentioning
confidence: 98%
“…We identified likely solid solutions in the system from cationic potential trends as described by Gaune-Escard et al The methodology allows the number and type of phases in salt mixtures to be estimated based on correlation with the cationic potential ratio for each experimentally known system involving CrCl 2 (Table ). The ratio is defined by eq : normalI normalP normalA normalI normalP Cr = z normalA / r normalA z Cr / r Cr where z is the cation charge and r is the 6-coordinated Shannon ionic radius .…”
Section: Resultsmentioning
confidence: 99%